Ectopic ACTH Secretion in a Child With Metastatic Ewing's Sarcoma: A Case Report - Di Ruscio, Valentina; Del Baldo, Giada; De Pasquale, Maria Debora; De Vito, Rita; Miele, Evelina; Colafati, Giovanna Stefania; Deodati, Annalisa; De Ioris, Maria Antonietta; Tornesello, Assunta; Milano, Giuseppe Maria; Mastronuzzi, Angela (Frontiers in Oncology, 2020)
Ectopic ACTH syndrome is rare in pediatric age. Sarcomas causing Ectopic ACTH Syndrome (EAS) are even uncommon. At the current time, only three cases of EAS caused by Ewing’ sarcoma are reported. We describe a 10-year-old boy presenting with Cushing's syndrome caused by ectopic ACTH production by a metastatic Ewing's sarcoma of the right ischio-pubic and ileo-pubic branches. Rapid appearance of cushingoid symptoms, with rapid weight gain, acne, hirsutism, and hypercortisolism with high levels of ACTH and non-suppression high dose dexamethasone test were diagnostic for ectopic ACTH production as paraneoplastic Cushing's Syndrome. We underline the possibility of EAS caused by an ACTH-secreting tumor, including soft tissue sarcomas.